Quantitative Management of Bond Portfolios - Dynkin, Lev; Gould, Anthony; Hyman, Jay; Phelps, Bruce (Princeton University Press, 2020)
The practice of institutional bond portfolio management has changed markedly since the late 1980s in response to new financial instruments, investment methodologies, and improved analytics. Investors are looking for a more disciplined, quantitative approach to asset management. Here, five top authorities from a leading Wall Street firm provide practical solutions and feasible methodologies based on investor inquiries. While taking a quantitative approach, they avoid complex mathematical derivations, making the book accessible to a wide audience, including portfolio managers, plan sponsors, research analysts, risk managers, academics, students, and anyone interested in bond portfolio management. The book covers a range of subjects of concern to fixed-income portfolio managers--investment style, benchmark replication and customization, managing credit and mortgage portfolios, managing central bank reserves, risk optimization, and performance attribution. The first part contains empirical studies of security selection versus asset allocation, index replication with derivatives and bonds, optimal portfolio diversification, and long-horizon performance of assets. The second part covers portfolio management tools for risk budgeting, bottom-up risk modeling, performance attribution, innovative measures of risk sensitivities, and hedging risk exposures. A first-of-its-kind publication from a team of practitioners at the front lines of financial thinking, this book presents a winning combination of mathematical models, intuitive examples, and clear language
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Aug 2020)
Keywords: BUSINESS & ECONOMICS / Finance / General; Bonds; Portfolio management